SHOULD ISLAMIC ACCOUNTING STANDARD FOLLOW TO INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS)? A LESSON FROM MALAYSIA - Dodik Siswantoro; Shahul Hameed Mohamed Ibrahim (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
It has been clearly shown that financing based Islamic teaching has inherentcharacteristics as well as its accounting. For that reason, it may not be so easy to convert Islamic accounting standard into International Financial Reporting Standard (IFRS) as it may violate some basic principles of Islamic teaching.Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) still commits to have different accounting standard as it is based on the fiqh (maxims). Furthermore, some countries adopt directly or indirectly the concept in IFRS, for example, in Malaysia. This paper tries to show some evidences on accounting standard which does not have a strong foundation of Islamic teaching would like probably to change by its milieu, especially in the IFRS convergence trend. This is because Islamic accounting standard itself merely based on “the convention” of the so called Islamic scholars.